Eu2P2S6: The First Rare‐Earth Chalcogenophosphate Exhibiting Large Second‐Harmonic Generation Response and High Laser‐Induced Damage Threshold. Issue 32 (28th June 2022) - Huang, Xiao; Yang, Si‐Han; Li, Xiao‐Hui; Liu, Wenlong; Guo, Sheng‐Ping
Abstract: Metal chalcogenophosphates are receiving increasing interest, specifically as promising infrared nonlinear optical (NLO) candidates. Here, a rare‐earth chalcogenophosphate Eu2 P2 S6 crystallizing in the monoclinic noncentrosymmetric space group Pn was synthesized using a high‐temperature solid‐state method. Its structure features isolated [P2 S6 ] 4− dimer, and two types of EuS8 bicapped triangular prisms. Eu2 P2 S6 exhibits a phase‐matchable second‐harmonic generation (SHG) response ≈0.9×AgGaS2 @2.1  μ m, and high laser‐induced damage threshold of 3.4×AgGaS2, representing the first rare‐earth NLO chalcogenophosphate. The theoretical calculation result suggests that the SHG response is ascribed to the synergetic contribution of [P2 S6 ] 4− dimers and EuS8 bicapped triangular prisms. This work provides not only a promising high‐performance infrared NLO material, but also opens the avenue for exploring rare‐earth chalcogenophosphates as potential IR NLO materials. Abstract : Eu2 P2 S6 exhibits excellent NLO properties, including a phase‐matchable second‐harmonic generation (SHG) response ≈0.9×AgGaS2 @2.1  μ m, and a high laser‐induced damage threshold of 3.4×AgGaS2 . Eu2 P2 S6 is the first NLO‐active rare‐earth‐based chalcogenophosphate.